Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s41983-022-00498-2
|View full text |Cite|
|
Sign up to set email alerts
|

Primary headache disorders in epileptic adults

Abstract: Background Epilepsy and primary headache disorders are two relatively common neurological disorders and their relationship is still a matter of debate. We aimed to estimate the prevalence and clinical features of primary headache disorders in patients with epilepsy. Methods 62 subjects aged ≥ 18 years were recruited from the hospital’s neurology outpatient clinic in the period from January to April 2018. The subjects were further divided into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…After publication of this article [1], the authors identified an error in the author name of Ahmed Osama.…”
mentioning
confidence: 99%
“…After publication of this article [1], the authors identified an error in the author name of Ahmed Osama.…”
mentioning
confidence: 99%